FISHERY AND BIOLOGY OF PENAEID PRAWNS AT HARNAII, MAHARASHTRA - Deshmukh, V. D.; Hule, A. S.; Mane, S. J.; Sawant, M. S. (Journal of Indian Fisheries Association, 2015)
Penaeid prawn fishery at Harnaii in Ratnagiri District of Maharashtrawas investigated during fishing seasons of 2002-03 and 2003-04 from mechanized(MLD) and hand operated trawlers (HT). During the two years, MLDcontributed 86% and HT 14% to the average annual penaeid prawn catch of2,242 t. The '?atch showed two peaks, a major during October-December anda minor during April-May in both the gears but abundance of the individualspecies differed.P. stylifera, M. affinis, S. crassicornis, M. brevicornis, P. merguiensis andM. dobsoni mainly constituted the fishery and their species composition,seasonal abundance, annual size distribution and monthly mean size wereinvestigated. Biological studies on food, size at maturity, spawning period,sex-ratio and juvenile abundance were carried out to Â·explain temporalabundance of the species in the fishery. Among the species P. stylifera, M.affinis and S. crassicornis exhibited distinct seasonality with two spawningpeaks, one in pre-monsoon and the other in post monsoon period to producetwo discrete broods while P. merguiensis despite two spawning peaksexhibited a single dominant brood. M. brevicornis showed monsoon and postmonsoonspawning while M. dobsoni showed only post-monsoon spawning.Migrations between nearshore and offshore waters resulted in mixing of thebroods and they remained inseparable in the catch.Keywords: penaeid prawn fishery, biology, spawning seasons, recruitabundance.